The Application and its Effects of Lecture Method in the Teaching Process at A Foundation University in Turkey - Tuncay Akçadağ (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
In this study, an application used in a lecture at a university was tried to be explained and the effects, thoughts, feelings, and criticisms that occurred in the students as a result of this application were tried to be determined. The steps of the developed application are as follows; the determination of the lesson objectives before the lesson by the teacher, the preparation of the evaluation questions for each lesson objective, the teacher’s entering the lesson by directing the evaluation questions to the students at the beginning of the lesson, making a short conversation about the answers given by the students to the evaluation questions, reminding students of the evaluation questions asked at the beginning of the lesson and enabling them to create answers again, comparing the first answers to the evaluation questions with the last answers, and enabling the students to see the differences between the answers. Qualitative research designs were used in the study. The required data were collected through analyzing the answers given to the questions of a semi-structured evaluation form based on the developed application from 73 students in different classes and courses from the education faculty of a foundation university in the 2019-2020 semester. The application was received positively by the majority of the students and their interest in the lectures increased. In addition, there were statements that the students were excited and had fun with the application, and they thought that the application should be expanded.